Pemanfaatan Pepaya sebagai Biostarter dalam Pengomposan Limbah Ikan dan Daun Mangrove Menggunakan Larva Black Soldier Fly - Mirna Apriani; Vivin Setiani; Farah Nabilla Thalib (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Fish waste generated from industrial activities in coastal communities has the potential to cause bad odors and pollute the environment. Falling mangrove leaves also contribute to waste in coastal areas because there are mangrove forests. This can pollute the environment so that fish waste and mangrove leaves can be processed through the composting method. Composting with BSF larvae can provide double benefits, namely reducing waste and producing larval feces that plants need. Papaya fruit waste that is no longer suitable for consumption can be used as a biostarter to speed up the decomposition process. The research variable was the use of 200 ml/kg papaya fruit biostarter. Variation in composition 100% mangrove leaves, 50% mangrove leaves; 50% fish waste, 70% mangrove leaves; 30% fish waste. Moisture content, temperature, pH, C/N, phosphorus, and potassium in several variations of this study met the quality of compost based on SNI 19-7030-2004. Based on MANOVA statistical analysis, variations in composition and type of biostarter influence larval biomass, feed consumption, and waste reduction index. Based on the quality of the compost, the best variation in this study was the composition of 50% fish waste compost and 50% mangrove leaves without the use of a biostarter.